P110 ACUTE EFFECT OF AEROBIC, RESISTANCE, AND COMBINED EXERCISE ON BLOOD PRESSURE AND VASCULAR RESISTANCE OF HYPERTENSIVE PATIENTS: RANDOMIZED CLINICAL TRIAL - Gustavo Waclawovsky; Bruna Eibel; Liliana Boll; Maximiliano Schaun; Eduardo Barbosa; Alexandre Lehnen (Artery Research, 2018)
Background: Exercise is part of antihypertensive therapy. However, little is known about the effect of different types of exercise on hemodynamic variables in systemic arterial hypertension (SAH). Purpose: To evaluate the effect of an aerobic (AE), resistance (RE) and combined (CE) exercise session on BP, blood flow (BF) and vascular resistance (VR) in hypertensive patients. Methods: Twenty-nine men with SAH randomly performed 40 min AE (60% of reserve heart rate) or 40 min RE (4 exercises, lower limbs, 4x12rep, 60% 1-maximal repetition) or 40 min CE (20 min ER [2x12rep] and 20 min EA). The BF, RV and BP were analyzed 10 min before, 5-25-55 min after the session. Doppler ultrasound videos were analyzed by CardiovasculareSuit™. Statistics: generalized estimation equation and post-hoc Bonferroni, p < 0.05. Results: No difference among groups for age: AE 42.13 ± 9.19, RE 42.63 ± 17.43, CE 45.29 ± 7.80; BMI: AE 28.95 ± 3.83, RE 31.03 ± 3.70, CE 30.73 ± 5,48; SBP: AE 131.82 ± 7.87, RE 133.41 ± 9.25, CE 133.20 ± 8.07; and DBP: AE 84.04 ± 10.50, RE 81,51 ± 10.12, CE 77.22 ± 8.06. Compared to baseline, there was a decreased in SBP with AE (25 min: 138.00 ± 5.59 vs. 128.40 ± 5.27 mmHg, p < 0,001; 55 min: 138.00 ± 5.59 vs. 131.50 ± 6.37 mmHg, p = 0.042) and increase for RE (5min: 138.10 ± 3.10 vs. 143.80 ± 3.21 mmHg, p < 0.001). Changes in DBP after AE (5min: 86.40 ± 3.15 vs. 79.00 ± 2,98 mmHg, p = 0.027). Increased in BF (5min: 190.18 ± 29.62 vs. 290.22 ± 36.06 mL/min, p = 0.001) and decreased in RV (5 min: 0.70 ± 0.14 vs. 0.41 ± 0.06 units, p = 0.017) after CE. Conclusions: AE provided reduction in SBP and DBP levels and CE led to increased BF and reduction in RV. These findings may indicate different acute vascular responses from types of exercise in SAH.